PENGARUH KEPUASAN DAN MINAT BELI TERHADAP LOYALITAS KONSUMEN SAYURAN HIDROPONIK: STUDI KASUS DI KOTA SURABAYA - Anggraini, Dian; Winarno, Sri Tjondro; Rizkiyah, Noor (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The growth of urban agriculture has driven an increase in demand for healthy vegetables such as hydroponics in the city of Surabaya. Despite the increasing trend of consumption, consumer loyalty is still a challenge affecting the sustainability of the market. This study aims to analyze the influence of satisfaction and buying interest on the loyalty of hydroponic vegetable consumers. The study was conducted on 103 respondents using the purposive sampling technique. The data was analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach to measure the relationship between latent variables. The results show that both consumer satisfaction and buying interest have a positive and significant influence on loyalty, with buying interest being the most dominant factor. An R² value of 0.745 indicates that the model has a high clarity of power over the loyalty variable, while a Q² value of 0.676 indicates the predictive power of the model. This research has a strategic impact for hydroponic agribusiness players to focus their marketing strategies on increasing purchase intention and satisfaction through education, product quality, and emotional approach to consumers. Theoretically, these findings strengthen the study of consumer behavior in the context of sustainable agribusiness in urban areas.